2018
DOI: 10.1002/lary.27423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Bilateral Meniere's Disease in a Single Asian Ethnic Group

Abstract: Objectives/Hypothesis To identify the clinical characteristics of patients with bilateral Meniere's disease (MD) in an Asian population. Study Design Cross‐sectional retrospective study. Methods We compared the clinical features of bilateral MD (BMD) and unilateral MD (UMD) in 320 Asian patients with single ethnicity. Demographic variables; age of onset; inner ear function; the coexistence of related disorders such as vestibular migraine, delayed MD, systemic autoimmune diseases, and familial MD; and prognoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
4
5
0
Order By: Relevance
“…Instead, we performed a comparative study with definite Meniere's disease to show the similarity of inner ear status between vestibular and of definite Meniere's disease. Nonetheless, according to the previous reports using the same inner ear MRI methods as the present study, the positivity rate of EH in healthy groups was 38.1% for c-EH and 7.1% for v-EH (16). Therefore, the positivity rates of c-EH (62.5%) and v-EH (68.8%) in our patients with vestibular Meniere's disease seem sufficiently higher than those in healthy controls.…”
Section: Limitations and Conclusionsupporting
confidence: 73%
See 1 more Smart Citation
“…Instead, we performed a comparative study with definite Meniere's disease to show the similarity of inner ear status between vestibular and of definite Meniere's disease. Nonetheless, according to the previous reports using the same inner ear MRI methods as the present study, the positivity rate of EH in healthy groups was 38.1% for c-EH and 7.1% for v-EH (16). Therefore, the positivity rates of c-EH (62.5%) and v-EH (68.8%) in our patients with vestibular Meniere's disease seem sufficiently higher than those in healthy controls.…”
Section: Limitations and Conclusionsupporting
confidence: 73%
“…In general, Meniere's disease affects one side of the ears. Several studies reported that the incidence of bilateral Meniere's disease was 2-47%, depending on the length of follow-up and strictness of adherence to the criteria for diagnosis (15,16). Recently, inner ear MRI scans have demonstrated the existence of EH in the unaffected ear in patients with Meniere's disease.…”
Section: Eh In Meniere's Diseasementioning
confidence: 99%
“…This agrees with our study. Usually, the second ear would be affected only to a mild tinnitus or fullness [17]. On the other hand, bilateral involvement was observed in about one third of MD cases.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune pathologies are considered to be related to MD, including autoimmune arthritis ( 4 ) and thyroid diseases ( 5 ). A familial predisposition to the development of MD has also been described ( 6 ), especially for BMD ( 7 , 8 ), and ethnic differences were shown in epidemiologic and genetic features ( 9 ). In addition, patients with BMD were reported to have a higher frequency of delayed MD ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…A familial predisposition to the development of MD has also been described ( 6 ), especially for BMD ( 7 , 8 ), and ethnic differences were shown in epidemiologic and genetic features ( 9 ). In addition, patients with BMD were reported to have a higher frequency of delayed MD ( 9 ). The concept of delayed MD is not different from delayed endolymphatic hydrops (DEH).…”
Section: Introductionmentioning
confidence: 99%